Diagnosis and Management of Ischemic Heart Disease - Lippi, Giuseppe; Franchini, Massimo; Cervellin, Gianfranco (Seminars in Thrombosis and Hemostasis, 2013)
Ischemic heart disease (IHD) is the leading cause of death and disability worldwide. An early and accurate diagnosis of IHD is necessary to improve outcomes. According to recent guidelines, the diagnosis of acute myocardial infarction (AMI) is based on increased or decreased value of cardiospecific troponins with one measure exceeding the 99th percentile upper reference limit, associated with symptoms suggestive for myocardial ischemia, indicative electrocardiogram abnormalities, and evidence of recent myocardial functional impairment or intracoronary thrombosis. The recent advent of highly sensitive troponin immunoassays has represented a paradigm shift, wherein the improved analytical sensitivity has increased the negative predictive value, while contextually decreasing the diagnostic specificity of these tests. Although several additional biomarkers have been proposed as surrogate or in combination with troponins, there is little evidence that any of these will substantially improve AMI diagnosis. With regard to therapy, early mechanical (i.e., percutaneous coronary intervention, PCI) or pharmacological reperfusion should be performed early in ST-segment elevation myocardial infarction (STEMI) within 12 h of symptom onset, whereas fibrinolysis may be considered in all other circumstances. Patients undergoing primary PCI should also receive a combination of double antiplatelet therapy (i.e., aspirin and adenosine diphosphate receptor blocker), associated with parenteral anticoagulation, preferably with low-molecular-weight heparin. In analogy with STEMI, a wealth of data shows that primary early invasive strategy (i.e., PCI) and antiplatelet therapy remains the cornerstone of management of patients with non-ST segment elevation acute coronary syndrome. Stem cell–based therapy has also emerged as a potentially therapeutic option, and there are ongoing efforts among several investigators to translate basic research into clinical practice.
Keywords: acute myocardial infarction; ischemic heart disease; acute coronary syndrome; diagnosis; therapy